Exploring The Self-Awareness Of Dental Students And House Surgeons Regarding Oral Cancer: A Qualitative Study On Control And Prevention Strategies - Gulmina Saeed Orakzai; Mariya Farooq; Misbah Ali; Syeda Munazza Gillani; Jayyad Salim Awal; Raif Ilyas (Journal of Rawalpindi Medical College)
Objective: This qualitative study is carried out to get insights regarding various factors contributing to the high prevalence of this cancer and preventive strategies by dental students and house officers.